MASALAH DALUARSANYA HAK PENUNTUTAN PADA KASUS PEMALSUAN TANDA TANGAN PADA SURAT DAN DUDUK PERKARANYA - Boy Bernard Carlos (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACTCode of Criminal Law (Penal Code) has set certain period of time on the subject of prosecution, can be expired by law. The provisions in article 78 of the Criminal Code actually set expiration rights of criminal prosecution, but should also be linked with the right run penalty. When the death of the right to run a longer sentence than the death of a criminal prosecution the right of the accused because it is definitely a mistake.Criminal fraud as governed by Article 263 of the Criminal Code was in fact a criminal act that should be done deliberately to to declare a person charged with the crime of forgery was proven, the public prosecutor and the judge must prove the existence of the will of the defendant to act as a false or falsified letter. The existence of the defendant's intent to use the letter as a letter of their own genuine and not faked or to make others use a letter that he created artificially, required the presence of the defendant's knowledge of the use of the letter that he made the false or that he can fake it cause harm.